LEARNING ENGLISH VOCABULARY USING MOBILE PHONES: SAUDI ARABIAN EFL TEACHERS IN FOCUS - Mansour Habbash (European Scientific Journal, ESJ, 2015)
As mobile connectedness continues to sweep across the landscape, the value of deploying mobile technology at the service of learning and teaching appears to be both self-evident and unavoidable. To this end, this study explores the effectiveness of using mobiles in teaching vocabulary in EFL (English as a Foreign Language) classes in Saudi Arabia. The main objective of this study is to find out the possibility of enhancing the students’ understanding of English vocabulary through mobile phone interface and to help them in using vocabulary items more precisely. The study examines the viability of the use of mobile phones in the EFL classes for the undergraduate students of the university of Tabuk for improving their English vocabulary. The subsidiary objectives are to determine whether the students and teachers find it comfortable and convenient to use mobile phones for educational purposes inside and outside the classrooms at the university. The required data were gathered by distributing a questionnaire to all the teachers engaged in EFL classes. The responses are analyzed by the qualitative interpretive method and the results are put for discussions with the aim of using the outcomes in constructing the course materials for future EFL studies and for providing the teachers with proper recommendations in preparing materials and in choosing relevant methods for their languages classes.